2008
DOI: 10.1111/j.1365-2710.2008.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of pharmacy shopping behaviour

Abstract: Pharmacy shopping behaviour is limited in the Netherlands. However, it may put the patient at risk for unintentional problems, such as drug-drug interactions with anti-infectives. A small proportion of patients exhibit possibly intentional shopping behaviour with psychotropic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 17 publications
(17 reference statements)
1
102
1
Order By: Relevance
“…Despite their young age, many drivers in our study had a history of previous DUID investigations: an indication in itself of problematic drug use. This is consistent with previous research showing that dDrug diversion (Buurma et al, 2008;Hall et al, 2008;Rönkä et al, 2015), substance use disorders (Compton et al, 2007), risk-taking behaviour, traffic accidents (Turner and McClure, 2003) and drug-impaired driving (Jones, 2005) are all more common in the young. A higher utilization of prescription drugs from illegal sources, including the Internet, and a more restrictive prescribing of psychoactive drugs in the young, may further contribute to the effect of age in our studyexplain our results.…”
Section: Main Findings and Their Interpretationsupporting
confidence: 82%
See 2 more Smart Citations
“…Despite their young age, many drivers in our study had a history of previous DUID investigations: an indication in itself of problematic drug use. This is consistent with previous research showing that dDrug diversion (Buurma et al, 2008;Hall et al, 2008;Rönkä et al, 2015), substance use disorders (Compton et al, 2007), risk-taking behaviour, traffic accidents (Turner and McClure, 2003) and drug-impaired driving (Jones, 2005) are all more common in the young. A higher utilization of prescription drugs from illegal sources, including the Internet, and a more restrictive prescribing of psychoactive drugs in the young, may further contribute to the effect of age in our studyexplain our results.…”
Section: Main Findings and Their Interpretationsupporting
confidence: 82%
“…As opposed to other substance use disorders, however, prescription drug abuse has reported as equal in both sexes (Cepeda et al, 2012;Hall et al, 2008;Han et al, 2014;Rönkä et al, 2015) or greater in women (Buurma et al, 2008;Worley and Thomas, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous research by Buurma et al 21 showed that the majority of Dutch patients is loyal to one pharmacy. In 2001 only 11% of the beneficiaries of a Dutch health insurance company visited more than one pharmacy, and for those who did, it mostly was a one-time visit to a second pharmacy.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
“…Pharmacy records have a high degree of completeness with regard to dispensed drugs. 21 All drugs were coded according to the WHO Anatomic Therapeutic Chemical (ATC) classification system. Persons were defined as user of a certain drug class if they filled at least one prescription in the year around the medical examination (between 6 months before and 6 months after the examination).…”
Section: Measurementsmentioning
confidence: 99%